EDUKASI KESEHATAN TENTANG ANEMIA PADA REMAJA PUTRI - wahida, Wahida; Gusriani, Gusriani; Noviyanti, Nur Indah (Universitas Borneo Tarakan, 2022)
Anemia is a condition in which the amount of hemoglobin (Hb) in the blood is below normal. Adolescent girls are at risk for iron deficiency anemia. According to WHO, the normal hemoglobin level for women over the age of 15 is 12.0 g/dl (7.5 mmol). Nutrition knowledge education can increase nutrition knowledge and prevent anemia in adolescent girls. The stages of this service include: Survey of schools that will be given education, Collecting data on adolescent problems in SMA 1 Kalukku, Consulting and licensing to provide education and early detection through Hb checks, Preparation of materials, methods, and tools used for counseling and examinations , Implementation of counseling activities, blood pressure checks and early detection of anemia as well as Evaluation of the implementation of counseling activities and early detection The evaluation of PkM activities uses observation sheets. The results of the examination of the Hb levels of adolescent girls showed that from 62 female adolescents, 38 (61.29%) were not anemic, 18 (29.03%) had mild anemia and 6 (9.6%) were moderately anemic. The results of the questionnaire showed that 59.2% of participants had poor knowledge and 40.8% had good knowledge and after being given education there was an increase in the knowledge of young women, namely 30.3% had less knowledge and 69.7% with good knowledge. After being given education, there was an increase in the knowledge of young women from 59.2% to 30.3% with less knowledge. Furthermore, from 40.8% to 69.7% for good knowledge. Increased knowledge of adolescent girls about anemia is expected to prevent or reduce the incidence of anemia in adolescent girls in the district Mamuju.